Simple Pictorial Depression Assessment Tool (Mood face set) - boonyong, sukontip (Academic Psychiatry and Psychology Journal, 2015)
Objectives: To determine the diagnostic accuracy of the Simple Pictorial Depression Assessment Tool (Mood face set) screening for depression in Thai community. Methods: The screening test study was conducted in 120 people ≥ 18 years of age that come to the outpatient department of Suanprung Psychiatric Hospital (exclude Schizophrenia and Mental retardation) from May through July, 2014. The participants were assessed for their depressive mood by the Simple Pictorial Depression Assessment Tool (Mood face set) and the Thai version of the Patient Health Questionnaire (PHQ-9). Then the diagnosis (depression or no depression) was performed by psychiatrists. All data were collected and analyzed for sensitivity, specificity, likelihood ratios for positive and negative results, and Area Under receiver operating characteristic Curve (AUC) with 95% confidence interval (95% CI). Results: The mean age of the participants was 44.9 years (SD = 13.3) and 57.5 % of them were females. Depression was found in 64 subjects, and no depression in 56 subjects. The depressive mood assessment by this screening took, an average of approximately 10 seconds. The optimal cut-off point of Mood face set was picture No.4 that showed a sensitivity of 78.1% (95% CI 68.0 - 88.3), specificity of 83.9% (95% CI 74.3 - 93.6), positive likelihood ratio of 4.9 (95% CI 2.6 - 8.9) and negative likelihood ratio of 0.3 (95% CI 0.2 - 0.4). The area under the curve (AUC) in this screening test was 0.8 (95% CI 0.7 – 0.9). The average time to complete the PHQ-9 was approximately 5 to 10 minutes. The accuracy of PHQ-9 showed a sensitivity of 78.1% (95% CI 68.0 - 88.3), specificity of 75.0% (95% CI 63.7 - 86.3), positive likelihood ratio of 3.1 (95% CI 1.9 - 5.0), and negative likelihood ratio of 0.3 (0.2 - 0.5). The AUC of PHQ-9 was 0.9 (95% CI 0.8 - 0.9). Conclusion: The Simple Pictorial Depression Assessment tool (Mood face set) has reliable diagnostic accuracy in screening depression for use in general practice. This tool took less time than PHQ-9, is of simple use and has no language or cultural barrier. It can, therefore, be used instead of PHQ-9, because there is no statistical significant difference in accuracy. Keywords: Pictorial, Depression Assessment Tool